Behavioral study of Cebus nigritus (Goldfuss, 1809) (Primates, Cebidae) in captivity - Santos, Livia Bertolla; dos Reis, Nelio Roberto (My University, 2009)
The objective of this study was to describe the behavior of Cebus nigritus kept in captivity. The work, carried out during the month of March 2008 at "Dr. Belrio Guimaraes Brandao" County Zoo in GarYa- SP and Monte Alegre Farm Ecological Park in Telemaco Borba- PR, included 48 hours of observations, divided equally in four daytime periods. The behavioral catalogue used was constituted of different categories such as: foraging, feeding, locomotion, rest, social interaction, physical care, alertness, manipulation of things, reproductive behavior and stereotyped behavior. Animals showed activities of foraging, feeding, and locomotion and social interaction in low percentages in the two morning periods; however, their frequencies increased in the afternoon. Other activities like physical care, alertness and stereotyped behavior appeared mainly in the two morning periods, but were reduced in the afternoon. The rest category was more evident early morning and late afternoon. Since the stereotypical behavior presented high percentages, this study recommends that the number of individuals be diversiied in the social organization of the groups and that environment enriching activities be developed in captivity, creating situations similar to the animal's natural habitat.